Computation of compressible flows using euler solvers on unstructured and adaptive meshes - Huang, Daniel Hai. (2009)
In the present study, a two-dimensional unstructured grid generator and a corresponding Euler solver have been developed and tested. Based on these, a three-dimensional un-structured grid generator and a three-dimensional Euler solver have also been developed and validated.